The processing of homicide in American courts - Oramas Mora, Daniela (Routledge handbook of homicide studies, 2024)
Here, we review the court system’s processing of homicide based on the findings of a systematic review of the existing literature that examines the various stages in the adjudication and sentencing process of homicides in the United States. There is an abundance of research, particularly in the area of sentencing; yet, there are still questions that need to be answered. As mentioned at the outset, due to its severity, the adjudication and sentencing process of homicide cases can serve as a barometer for national practices. Homicides also often receive public attention, so criminal justice officials have less discretion in handling these cases. One can assume that the decision-making process is “purer” and can provide a clearer insight into the working of American Court systems. Moreover, given the seriousness of homicide and the detrimental effects it has on surviving family and friends of victims, and society as a whole, it is imperative to understand the processing of these cases to develop best response practices that can help survivors achieve justice for their loved ones.